Close-up : great cinematic performances. - Pomerance, Murray, 1946-; Stevens, Kyle (Edinburgh University Press, 2018)
The first systematic analysis of current debates surrounding the role of practice in political theory.
Keywords: Motion picture acting.; Motion picture acting -- Case studies.; Motion pictures -- History.; Motion pictures -- History -- Case studies.; Art de l'acteur au cinéma.; Art de l'acteur au cinéma -- Études de cas.; Cinéma -- Histoire.; Cinéma -- Histoire -- Études de cas.; PERFORMING ARTS -- Reference.; PERFORMING ARTS / Acting & Auditioning; Motion picture acting; Motion pictures; Case studies; History